A simple pre-sodiation strategy to improve the performance and energy density of sodium ion batteries with Na4V2(PO4)3 as the cathode material. Issue 44 (2nd November 2020) - Mirza, Shahid; Song, Zihan; Zhang, Hongzhang; Hussain, Arshad; Zhang, Huamin; Li, Xianfeng
Abstract : A pre-sodiation strategy of using Na4 V2 (PO4 )3 cathode to compensate the irreversible capacity loss of hard carbon anode is demonstrated and improves the energy density of sodium ion batteries. Abstract : Sodium-ion batteries are considered surrogates for conventional lithium-ion batteries for the commercial sector. One of the most favourable anode materials for sodium-ion batteries is hard carbon. However, its performance is affected by the large irreversible capacity loss (ICL) in the initial charge process. This study proposes the Na4 V2 (PO4 )3 (Na4VP) cathode as a possible solution for matching the hard carbon anode. The process uses a recently developed electrochemical pre-sodiation strategy, where the first step converts Na3 V2 (PO4 )3 (Na3VP) to a Na4VP cathode by a sodiation step. After this, a de-sodiation step of Na4VP is carried out below 2.2 V ( vs. Na + /Na) to entirely compensate for the ICL of the anode, and the resulting Na3VP directly acts as the cathode. As a result, the Na4VP‖HC full cell achieves a substantially high specific energy of 265 W h kg −1, which is 76% higher than that of the Na3VP‖HC full cell. Moreover, the Na4VP‖HC full cell shows excellent rate performance (62.32 mA h g −1 at 10C) and cycling stability (about 80.0% capacity retention after 100 cycles at 1C). This work is a precursor to the further study of other battery and hybrid capacitor systems, where pre-sodiation plays an important role in improving their performance.